3D Printed concrete with coarse aggregates: Built‒in‒Stirrup permanent concrete formwork for reinforced columns. (1st July 2023) - Chen, Yidong; Zhang, Wenhua; Zhang, Yunsheng; Zhang, Yu; Liu, Cheng; Wang, Dafu; Liu, Zhiyong; Liu, Guojian; Pang, Bo; Yang, Lin
Abstract: This paper investigates the axial compression performance of reinforced columns with 3D‒printed permanent concrete (with coarse aggregate) formwork. A novel square stirrup with reserved longitudinal reinforcement holes and its built‒in‒stirrup permanent concrete formwork method (BSPCF) were presented. Reinforced columns using BSPCF, only 3D printed permanent concrete formwork (3DPCPF), and conventional cast were manufactured and tested by axial compression experiments. Digital image correlation (DIC) was used to obtain the full‒field strain evolution of concrete columns during loading and the results were confirmed by comparison with traditional measurement methods. Results indicated that the column with only 3DPCPF faced concrete formwork early spalling and severe bearing capacity reduction problems. Using BSPCF could adequately avoid the above problems and enhance the column bearing capacity close to that of conventional cast concrete columns. The DIC measurement accurately detected the interlayer fracture of the 3DPCPF under axial compression, which might be responsible for the sudden main crack development. Subsequently, a calculation method suitable for evaluating the effective part of the thicker concrete cover was proposed and discussed. The sudden decrease in aggregate content and increase of voids in the interface region between the confined core concrete and the 3D-printed concrete formwork of columns were found by X-ray computed tomography (X-CT). This phenomenon further proved the importance of BSPCF in lateral stress transfer passing over the interface region. Highlights: A novel square stirrup and its built-in-stirrup permanent concrete formwork method (BSPCF) were presented. The axial compression test verified the effectiveness of BSPCF in 3D printed reinforced columns. Digital image correlation (DIC) further compared the full‒field strain evolution of columns manufactured in three methods. X-CT results revealed reasons for the early spalling of columns with only permanent external 3D printed formwork.